Building back better from COVID-19: Knowledge, emergence and social contracts. (February 2022) - Pelling, Mark; Adams, Helen; Adamson, George; Barcena, Alejandro; Blackburn, Sophie; Borie, Maud; Donovan, Amy; Ogra, Anshu; Taylor, Faith; Yi, Lu
COVID-19 recovery is an opportunity to enhance life chances by Building Back Better, an objective promoted by the UN and deployed politically at national level. To help understand emergent and intentional opportunities to Build Back Better, we propose a research agenda drawing from geographical thinking on social contracts, assemblage theory and the politics of knowledge. This points research towards the ways in which everyday and professional knowledge cocreation constrains vision and action. Whose knowledge is legitimate, how legitimacy is ascribed and the place of science, the media and government in these processes become sites for progressive Building Back Better.